Impact of Hypertension on COVID-19 Burden in Kidney Transplant Recipients: An Observational Cohort Study - Isabella Aguiar-Brito; Débora D. de Lucena; Alexandre Veronese-Araújo; Marina P. Cristelli; Hélio Tedesco-Silva; José O. Medina-Pestana; Érika B. Rangel (Viruses, 2022)
Background: COVID-19 severity is determined by cardiometabolic risk factors, which can be further aggravated by chronic immunosuppression in kidney transplant recipients (KTRs). We aimed to verify the main risk factors related to hypertension (HTN) that contribute to COVID-19 progression and mortality in that population. Methods: Retrospective analysis of 300 KTRs from March 2020 to August 2020 in a single center. We compared the main outcomes between HTN (n = 225) and non-HTN (n = 75), including admission to the intensive care unit (ICU), development of acute kidney injury (AKI), need for invasive mechanical ventilation or oxygen, and mortality. Results: Of the patients in the study, 57.3% were male, 61.3% were white, the mean age was 52.5 years, and 75% had HTN. Pre-existing HTN was independently associated with higher rates of mortality (32.9%, OR = 1.96, p = 0.036), transfer to the ICU (50.7%, OR = 1.94, p = 0.017), and AKI with hemodialysis (HD) requirement (40.4%, OR = 2.15, p = 0.011). In the hypertensive group, age, diabetes mellitus, heart disease, smoking, glycemic control before admission, C-reactive protein, lactate dehydrogenase, lymphocytes, and D-dimer were significantly associated with COVID-19 progression and mortality. Both lower basal and previous estimated glomerular filtration rates posed KTRs with HTN at greater risk for HD requirement. Conclusions: Therefore, the early identification of factors that predict COVID-19 progression and mortality in KTRs affected by COVID-19 contributes to therapeutic decisions, patient flow management, and allocation of resources.